Using vitamin C and sodium bentonite as food additives in the diets of common carp Cyprinus carpio L. - Al_Dubakel, A.Y. Al_Dubakel; Al_Sanaban, M.A . (Iraqi Journal of Aquaculture, 2022)
An experiments were conducted in open culture system to study the effect of food additives i.e. vitamin C and sodium bentonite to improve the diets characteristics of common carp Cyprinus carpio in concentrations 100, 250 and 500 mg vitamin C/ kg diet and 10, 20 and 30 gm S.B./ kg diet. The results indicate that there was a significant differences (P<0.01) between diets contain additives superior than diets without it (control) the weight increase in fish were 49.03 gm(500 mg vitamin C), 50.79 gm ( S.B. 30 gm) while it was 40 gm in control diets. Also the values of relative growth rates increased (38.35, 40.23 and 31.33 % respectively) and specific growth rats (0.46, 0.48 and 0.39 % wt/day respectively). A distinct effect was noticed of these additives on the food conversion ratio (FCR), protein efficiency ratio (PER) and productive protein value (PPV).While no significant differences (P>0.01) were noticed between diets in food in take which ranged between 2.62 to 3.43 % from body weight .The body protein levels were increased (16.36 – 21.00 %) compared to it level before experiments (15.59) .The diets contain all levels of vit.C and 20 gm of sodium bentonite showed high protein digestibility. The feces weight increased with vit.C level but decreased with sodium bentonite level. It was concluded from the present study that food additives are economically important to increase growth and food efficiency which in turn lowering fish production cost.